Extraction Of Collagen From Quail (Coturnix Japonica) Feet: Characterization And Development Of Electrospun Nanofibers - Borbori, Mahsa Yousefi (2019)
Poultry processing plants produce a huge amount of wastes. The discharge of these amounts of wastes has raised serious concerns regarding their environmental impacts, diseases, and loss of valuable biological resources like proteins and lipids. Utilization of these by-products for producing value-added products may offer a feasible and economically viable solution. This line of thought led to the research on the by-products as sources of collagen. In this study, quails’ feet from poultry processing by-products was utilized as a new source of collagen along with other applications such as electrospun nanofibers. In this way, acid and pepsin soluble collagens and also lactic acid and lactic acid pepsin soluble collagens were extracted from quails’ feet and characterized. The physicochemical, thermal and morphological properties of the extracted collagens are investigated. The electrophoretic patterns indicated that all samples were type-I collagen with three different chains. Amino acid analysis demonstrated that the imino acid contents of the samples are higher than those of calf-skin, pig-skin, and chicken feet collagens. The FTIR spectra suggested that the extracted collagens were in triple-helical structure. The zeta-potential analysis is shown the isoelectric points of the collagens are in the pH range of 5.24-5.61. Differential scanning calorimetry and thermogravimetric analyses indicated that the extracted collagens had higher thermal stability in comparison to calf-skin and pig-skin collagens. The result showed that the correlation between the thermal stability of collagen and the imino acid content.